Planktonic Protists of the Eastern Nordic Seas and the Fram Strait: Spatial Changes Related to Hydrography During Early Summer - Dąbrowska, Anna Maria; Wiktor, Józef Mikołaj; Merchel, Małgorzata; Wiktor, Józef Maria (Frontiers in Marine Science, 2020)
The European Arctic is rapidly changing where increasing water temperatures and rapid loss of sea-ice will likely influence the structure and functioning of the entire ecosystem. This study aimed to describe the taxonomic composition and spatial distribution of early summer (2015-2016) nano- and microplanktonic protists in the Nordic (Norwegian, Greenland) Seas and the Fram Strait (70.99°N to 78.84°N; 1.52°E to 19.90°E) and to determine the distribution patterns of the communities from the aspect of hydrography, as deduced from in situ measurements. Here we identify some generalized regularity in the protistan distribution, indicating the two separated domains at the 6 °C threshold. While Phaeocystis seemed to be a fairly conservative representative of the colder area (< 6 °C), the taxonomic structure of the warmer waters (> 6 °C) may vary significantly between successive summers: from mostly Bacillariophyceae-dominated communities in 2015 to flagellate-dominated in 2016. Based on our results, we hypothesised that the more intense phototrophs development in the area, as deduced from higher remotely sensed chlorophyll a concentrations in 2016, i.e., record warm year in the observational period, could lead to faster depletion of nutrients, and thus, an earlier shift into the post-bloom community stage. Taking into account the possible phenological shift towards early summer domination of flagellates in a warmer year, as well as a higher number of heterotrophic protists associated with the warmer domain in two evaluated summers, it is highly likely that climatic warming of this region will have an impact on energy transfer to higher trophic levels. Although generalized patterns could be elucidated, more information is needed to predict and understand how the changing Arctic will alter protistan communities, and thus, higher-order consumers.